Be inFLUential: Evaluation of a multifaceted intervention to increase influenza vaccination rates among pediatric inpatients. Issue 6 (5th February 2020) - Rao, Suchitra; Ziniel, Sonja I.; Khan, Isra'a; Dempsey, Amanda
Highlights: Intervention consisted of reminders, automated orders and audit and feedback methods. Led to a 21% increase in influenza vaccine ordering, and a 9% increase in overall vaccination rates. Ordering rates were highest among residents and general medical teams. Abstract: Background and Objective: Annual influenza vaccination is recommended for individual ≥6 months of age, yet vaccination rates remain below national targets in the US. Hospitalization provides another medical setting for influenza vaccination, but the effectiveness of inpatient interventions has not been well studied. Our objective was to evaluate the effectiveness of a multifaceted intervention to increase influenza vaccination rates among pediatric inpatients. Methods: We conducted a pre-post interventional study on medical inpatient units at Children's Hospital Colorado from September 2016-April 2017 (pre-intervention) and September 2017-April 2018 (intervention). The intervention targeted nurses (web-based education modules, huddles and reminders) and providers (vaccination lists in the electronic health record, reminders, vaccination reports and financial incentives for residents). Outcomes were influenza vaccine ordering rates, and influenza vaccination rates at discharge. We analyzed data using descriptive statistics, bivariate and logistic regression. Results: Among 4, 050 inpatients in 2016–2017 and 4, 523 inpatients in 2017 aged ≥ 6 months, vaccination status was documented for 2, 902/4, 050 (71.7%) and 3, 431/4, 523 (75.9%) children aged > 6 months of age hospitalized during the study period. The vaccine ordering rate among eligible children was 28.8% in the pre-intervention season versus 50.2% in the intervention season (p < 0.001). The intervention was associated with 1.23 (95% CI 1.11–1.35) times higher odds of appropriate vaccination screening on admission, 2.27 (95% CI 2.01–2.56) times higher odds of a vaccination being ordered, and 1.39 (95% CI 1.27–1.53) times higher odds of a child being vaccinated against influenza at discharge (all p < 0.001). Residents (56%) and medical providers (39%) were more likely to order vaccines compared with nurses (5%), p = 0.014). Conclusion: A multifaceted intervention targeting nurses, residents and providers comprising education, visual reminders, vaccination reports and financial incentives is an effective way of improving influenza vaccine ordering, resulting in higher inpatient influenza vaccination rates.